The presence of lice species on wild geese in the Elazi? district - Aksin, Nursel (My University, 2004)
The purpose of this study was to determine the presence of lice species on wild geese in the Elazi? district. Twenty wild geese were inspected for lice species between January and February in 1998 and 2001. Nine of these geese had been exposed to lice infestations and Anaticola anseris (Linnaeus, 1758) composed all the collected 92 lice. The morphological description of A. anseris was based on microscopy and microphotography pictures were taken.
Elazi? yöresinde yabani kazlarda bit enfestasyonu
Keywords: Anaticola anseris; Goose; Lice